The ABC of academic procrastination: Functional analysis of a detrimental habit - Svartdal, Frode; Løkke, Jon Arne (Frontiers in Psychology, 2022)
Academic procrastination – habitually delaying work with academic tasks to the extent that the delays become detrimental to performance, wellbeing, and health – represents a substantial personal, systemic, and societal problem. Still, efforts to prevent and reduce it are surprisingly scarce and often offered as treatment regimens rather than preventive efforts. Based on the principles of functional analysis and a broad examination of factors that are important for academic procrastinatory behaviors, this paper aims to describe a strategy for analyzing individual controlling conditions for procrastination and give parallel advice on how to change those controlling conditions. Both are ideographic, allowing for individual and dynamic analyses of factors responsible for instigating and maintaining procrastination, as well as tailor-made remedies that address controlling conditions in preventive and curative efforts to reduce procrastination. Although functional analysis integrates well with important research findings in the procrastination field, this approach suggests new criteria for identifying procrastinatory behaviors and an alternative model for analyzing their control conditions. We conclude that a functional approach may supplement procrastination research and efforts to prevent and alleviate this detrimental habit.